Optimization of nanoemulsion hair serum from chia seed oil using the Simplex Lattice Design method - Rahmayanti, Mayu; Oktavia, Reza Putri; Amalina, Faidatul; Fadila, Safa Aulia Nur; Nastiti, Ginanjar Putri; Syarifuddin, Sadli (Universitas Ahmad Dahlan, 2024)
Hair loss is a hair problem that men and women often experience. Chia seed oil (Salvia hispanica L.) contains linolenic acid, which can stimulate the sebum glands. This research aims to determine the composition of the optimum formula for chia seed oil nanoemulsion hair serum using the Simplex Lattice Design (SLD) method to prove that the characteristics and physical stability of the optimum formula meet the requirements for good preparation. The optimization method was carried out with the help of Design Expert 13 software to optimize the formula by varying Tween 80 (X1) and propylene glycol (X2). The characteristic parameters observed include organoleptic parameters such as pH, viscosity, homogeneity, emulsion type, particle size, zeta potential, polydispersity index, and percent transmittance. The physical stability test was carried out using a 6-cycle test method for organoleptic parameters, pH, and homogeneity. Optimization results show that the optimum composition consists of Tween 80 33.52% and propylene glycol 46.48%. The preparation meets all physical characteristic tests. Physical stability did not significantly change in the pH test, with a significance value of 0.027 in the paired t-test. Based on the research results, it can be concluded that the optimum surfactant and cosurfactant composition in the optimum formula based on optimization using SLD is Tween 80 (33.52%) and propylene glycol (46.48%) with a desirability value of 0.947. The optimum formula for preparing chia seed oil nanoemulsion hair serum meets good physical characteristics and stability requirements.